Rola pielęgniarki w opiece nad pacjentem po zabiegu bariatrycznym - Kaszuba, Małgorzata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2024)
This article discusses obesity as a global health issue, recognised by the World Health Organisation as a disease, with an increasing trend among populations, especially in affluent countries. It highlights the role of nurses in caring for patients after bariatric surgery, analysing their support at each treatment stage. Nurses play a key role in preoperative, operative, and postoperative care, collaborating with other specialists and providing continuous care to patients. Nurses are essential in delivering comprehensive care to patients after bariatric surgery, facing challenges in team communication and the need for ongoing training. Telenursing stands out as a modern method to improve the quality of postoperative care.